2022
DOI: 10.1177/13524585211068002
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of a web-based mindfulness programme for people with MS with and without a history of recurrent depression

Abstract: Background: Evidence shows small positive effects associated with psychological treatments for people with multiple sclerosis (PwMS). In a recent meta-analysis, the treatment with the largest effect size was a mindfulness-based intervention (MBI). Objectives: We aimed to determine whether an Internet-delivered MBI was beneficial for PwMS. Furthermore, we aimed to investigate history of recurrent depression as a moderator of treatment outcome. Methods: Participants ( N = 132) were assessed based on whether they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Following deduplication and the addition of four further studies identified via reference list searching there were 1,312 potential studies for inclusion. After title and abstract screening, 30 full text studies were reviewed, of which 14 were included in the final analyses [50][51][52][53][54][55][56][57][58][59][60][61][62][63] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following deduplication and the addition of four further studies identified via reference list searching there were 1,312 potential studies for inclusion. After title and abstract screening, 30 full text studies were reviewed, of which 14 were included in the final analyses [50][51][52][53][54][55][56][57][58][59][60][61][62][63] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Eight of the 14 studies reported carrying out power calculations to determine necessary sample size [52, 55, 56, 58-60, 62, 63]; of the remaining, five did not [51,53,57,58,61] and one provided insufficient detail [54]. Studies took place across four continents, in eight different countries: three from Iran [54,57,63], two from Italy [55,56], the UK [51,53], Australia [59,61], the USA [50,60], and one each from Switzerland [52], Canada [62], and France [58]. Sample size ranged from 21-150.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Preliminary findings demonstrated that online MBIs can reduce anxiety and stress in healthy adults, adults with posttraumatic stress disorder symptoms, and adults with multiple sclerosis. 52 A recent review of RCTs concluded that web-based MBIs are as effective as in-person MBIs at reducing sleep disturbance and improving sleep quality. To our knowledge, the effectiveness of a web-based MBI has not been examined in poststroke patients, but several studies have addressed the feasibility and efficacy of web-based MBI for those who are undergoing treatment in a clinical setting.…”
Section: Methodsmentioning
confidence: 99%